The Gene Regulatory Network of Lens Induction Is Wired through Meis-Dependent Shadow Enhancers of Pax6 - Antosova, Barbora; Smolikova, Jana; Klimova, Lucie; Lachova, Jitka; Bendova, Michaela; Kozmikova, Iryna; Machon, Ondrej; Kozmik, Zbynek (PLoS genetics, 2016)
Lens induction is a classical developmental model allowing investigation of cell specification, spatiotemporal control of gene expression, as well as how transcription factors are integrated into highly complex gene regulatory networks (GRNs). Pax6 represents a key node in the gene regulatory network governing mammalian lens induction. Meis1 and Meis2 homeoproteins are considered as essential upstream regulators of Pax6 during lens morphogenesis based on their interaction with the ectoderm enhancer (EE) located upstream of Pax6 transcription start site. Despite this generally accepted regulatory pathway, Meis1-, Meis2- and EE-deficient mice have surprisingly mild eye phenotypes at placodal stage of lens development. Here, we show that simultaneous deletion of Meis1 and Meis2 in presumptive lens ectoderm results in arrested lens development in the pre-placodal stage, and neither lens placode nor lens is formed. We found that in the presumptive lens ectoderm of Meis1/Meis2 deficient embryos Pax6 expression is absent. We demonstrate using chromatin immunoprecipitation (ChIP) that in addition to EE, Meis homeoproteins bind to a remote, ultraconserved SIMO enhancer of Pax6. We further show, using in vivo gene reporter analyses, that the lens-specific activity of SIMO enhancer is dependent on the presence of three Meis binding sites, phylogenetically conserved from man to zebrafish. Genetic ablation of EE and SIMO enhancers demostrates their requirement for lens induction and uncovers an apparent redundancy at early stages of lens development. These findings identify a genetic requirement for Meis1 and Meis2 during the early steps of mammalian eye development. Moreover, they reveal an apparent robustness in the gene regulatory mechanism whereby two independent "shadow enhancers" maintain critical levels of a dosage-sensitive gene, Pax6, during lens induction.
Keywords: Zebrafish; nádorové proteiny; vazebná místa; vývojová regulace genové exprese; Eye; Myeloid Ecotropic Viral Integration Site 1 Protein; Gene Expression Regulation, Developmental; Gene Regulatory Networks; oční čočka; dánio pruhované; Ectoderm; transkripční faktor PAX6; transkripční faktor Meis1; Lens, Crystalline; zesilovače transkripce; ektoderm; genové regulační sítě; Binding Sites; Animals; lidé; Enhancer Elements, Genetic; oči; Humans; zvířata; myši; Neoplasm Proteins; Homeodomain Proteins; Mice; PAX6 Transcription Factor; homeodoménové proteiny